The attention to the appropriate data treatment is fundamental to possible achieve all the potential to the open science - Luiz Olavo Bonino da Silva Santos (Universidade Federal do Estado do Rio de Janeiro, 2018)
Since XVII century, the societies demand a grater opening and transparency for the academic activities. Considering that most of scientific founding come from government resources, it is natural that the society expects a better access to the elements that constitutes the scientific research, like data, experiments and results. This causes not only the society access to those results, but also that other scientists may reuse data and results of other researches in another different way and reach other conclusions. Therefore, a greater data reuse and results from a more opened scientific environment enables a more efficient and effective use of the resources invested.